Factors Related Factors With HIV/AIDS Risk Behavior In Adolescents - Adinda Mada Shafa Salsabila; Yoga Triwijayanti; Yetti Anggraini; M. Ridwan (Jurnal Maternitas Kebidanan, 2026)
HIV/AIDS is a global health problem that is still a serious concern, especially for adolescents who belong to vulnerable groups. This study aims to determine the factors associated with HIV/AIDS prevention risk behavior among adolescents. This type of research uses a quantitative approach with a Cross Sectional design. The population of this study were adolescents who visited the Ganjar Agung West Metro Health Center totaling 562, the research sample was 106 respondents with the sampling technique using Accidental Sampling. Data collection instruments in the form of questionnaires and data analysis using Chi-Square test. The results showed that 91.5% of adolescents had non-risk behaviors for HIV/AIDS prevention, the proportion of good peer roles was 84%, the proportion of positive attitudes was 56.6%, the proportion of good parental roles was 62%. Statistical test results there is a relationship between the role of peers (p-value = 0.005) and attitude (p-value = 0.010) with risky behavior of HIV/AIDS prevention in adolescents. There was no relationship between the role of parents (p-value = 0.158) and the risky behavior of HIV/AIDS prevention in adolescents. The conclusion of this study is that there is a significant relationship between the role of peers, attitudes with HIV/AIDS prevention risk behavior in adolescents and there is no relationship between the role of parents with HIV/AIDS prevention risk behavior in adolescents.